An updated database of Holocene relative sea level changes in NE Aegean Sea - Vacchi M.; Rovere A.; Chatzipetros A.; Zouros N.; Firpo M. (Quaternary International, 2014)
The reconstruction of Holocene relative sea levels has several implications, ranging from the investigation of coastal vertical movements to the calibration of earth rheology models and ice sheet reconstructions. The North Eastern Aegean Sea is among the tectonically complex sectors of the Eastern Mediterranean, mainly influenced by the activity of the North Anatolian Fault. In this paper, we created a relative sea level (RSL) database by expanding upon the previous compilation with recently published geological and archaeological data. We reconstruct the RSL history in those Aegean coastal sectors located within the South Marmara microplate, a broad shear zone located between western Anatolia and central Greece and affected by dominant strike-slip faulting, at times combined with a normal component. Then, we compared it with the RSL histories obtained for the surrounding coastal sectors. The analysis of the database indicated that it is not possible to define a common Holocene RSL curve for the entire NE Aegean, as RSL history here is majorly influenced by changes in deformation patterns. In addition, data in our database are consistent with a continuous RSL rise in the last 6.0 ka BP in the whole NE Aegean Sea and cannot support the hypothesis of a mid-Holocene RSL highstand in the area. Finally, we present our best estimates of late Holocene rates of RSL prior to any possible acceleration during the twentieth century in the broad area of NE Aegean. Here we identified the fastest rising rate (~0.9 mm a-1) in that sector whose active tectonic deformation is mainly controlled by the North Anatolian Fault activity. © 2013 Elsevier Ltd and INQUA.